The Model of Market Orientation, Entrepreneurial Orientation and Business Performance of Small and Medium Enterprises - Octavia, Ade; Ali, Hapzi (International Review of Management and Marketing, 2017)
Small and medium business in Indonesia has different characteristics with other countries. This research aims to analyze the influence between the orientation of the market and the business performance of small and medium enterprises. Entrepreneurial orientation variables used as the antecedent of market orientation and business performance as of the variable consequences. Design research using the survey sample and FGD with owners of small and medium enterprises as the respondent. By using SEM analysis found that entrepreneurial orientation effect directly against the performance of the business, but the orientation of the market does not have significant influence on performance of the business. Keywords: market orientation, entrepreneurial orientation, the performance of the business. JEL Classifications: L1, L25